Zarządzanie jakością w usługach publicznych w warunkach Nowego Zarządzania Publicznego: Quality management in public services in terms of the New Public Management - Klimek, Anna (Management and Administration Journal, 2021)
The purpose of this document is to give the essential aspects of the New Public Management. Work will present the characteristics of the public sector and will search for differences between public governance and quality management in public organizations. The authors also wanted to draw attention to the characteristics of the most important relationships in the management of public sector organizations, to explain concepts related to the New Management in the public sector and to show possible "dimensions" of quality management in public services.